Analisis Yuridis Terhadap Putusan Pengadilan Negeri Jambi Nomor: 276/Pid.Sus/2023/PN.Jmb Dalam Perkara Tindak Pidana Pencabulan Terhadap Anak - Febriani Sari, Indah Rizeki; Sahabuddin, S; Gani, Ruslan Abdul (Legalitas: Jurnal Hukum, 2024)
Children are a gift given by God Almighty, whether a man or a woman. Children are the future successors of the nation who will be the country's main asset to achieve prosperity in the future. Therefore, it is appropriate for children to receive good treatment by being cared for, educated, looked after and protected by the state. However, currently there is still a lot of violence against children, especially in the form of sexual violence. The objectives of the research are 1.) To find out and analyze how the judge considered in deciding case Number 276/Pid.Sus/2023/PN Jmb., 2.) To find out and analyze the judge's decision in case Number 276/Pid.Sus/2023/PN Jmb. has fulfilled the sense of justice or not